2015
DOI: 10.1093/jisesa/ieu173
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Chemical Compositions of Cassava Varieties to Their Resistance to Prostephanus truncatus Horn (Coleoptera: Bostrichidae)

Abstract: The preference of cassava as a major host by Prostephanus truncatus Horn is a major constraint to ample production of cassava, Manihot esculenta Crantz and storage. This study analyzed the nutritional and secondary metabolite compositions in 15 cassava varieties, evaluated levels of damage and reproduction by P. truncatus, and assessed their resistance to attack. One hundred grams of dried cassava chips in 250-ml Kilner jars were infested with 10 adult larger grain borerof 0–10 days old and held for 3 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Several studies had illustrated that metabolites such as flavonoids ( Gazola et al, 2019 ; Yang et al, 2020 ), phenylpropanoid ( Yang et al, 2019 ) and total tannin ( Osipitan et al, 2015 ) were responsible for cassava resistance to insect or mite species. However, there was a lack of further step to excavate and validate the specific compounds that definitely possessed bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had illustrated that metabolites such as flavonoids ( Gazola et al, 2019 ; Yang et al, 2020 ), phenylpropanoid ( Yang et al, 2019 ) and total tannin ( Osipitan et al, 2015 ) were responsible for cassava resistance to insect or mite species. However, there was a lack of further step to excavate and validate the specific compounds that definitely possessed bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to acknowledge that treatment of snake bites with plants has been unquestionable in the science domain, especially if there is evidence of metabolites such as alkaloids, flavonoids, or tannins [ 45 , 46 ]. Therefore, identification of cassava, which has alkaloids, flavonoid glycosides and tannins among others [ 7 , 9 ], being used to treat scorpion or snake bite in this community and reportedly used in India and Papua New Guinea is in tandem intercultural ethnopharmacology. However, to our knowledge and as indicated in our results, it has been scarcely known that medicinal value of cassava includes anti-venom properties.…”
Section: Discussionmentioning
confidence: 99%
“…Cassava has been known to contain alkaloids [ 7 , 8 ], as well as possessing cyanogenic and flavonoid glycosides [ 9 ]. It is also known that flavonoids have antioxidant and hypolipidemic effects [ 10 - 12 ], while glycosides are potent for heart disease [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Sugiura et al (2015) reported that consuming carotenoids-rich diets could protect against developing type 2 diabetes (T2D). Aside from the carotenoids in yellow-fleshed cassava, cassava flour also contains phenolic compounds (Irondi et al, 2019;Adefegha et al, 2021), flavonoid glycosides, alkaloids (Osipitan et al, 2015;Pinto-Zevallos et al, 2016), and fiber (Nwose et al, 2017); all of which are prominent for their health benefits. Most of the existing reports on these bioactive constituents, aside carotenoids, were on white-fleshed cassava root and its traditional products, leaving the bioactive components and bioactivities of yellowfleshed cassava genotypes under-reported.…”
Section: Introductionmentioning
confidence: 99%